Tracheal agenesis in a new born: lessons learnt. (17th June 2018) - Naina, P; John, Mary; Kathar, Mohamed Abdul; Kumar, Manish
Abstract : Tracheal agenesis is a rare but fatal congenital tracheal malformation. Lack of prenatal symptom and a typical clinical presentation lead to failure to arrive at a correct diagnosis and confusion during resuscitation. We report a case of a newborn male child with type 2 tracheal agenesis. Despite a typical presentation, diagnosis was delayed after unsuccessful intubation, examination under anaesthesia and emergency tracheostomy. The embryology, diagnostic criteria and potential treatment options are discussed. This case report is valuable in increasing awareness of this rare condition and will help us in being better prepared in managing these children. Future studies should aim to find the optimal replacement for the tracheal.